Investigating the Quality of General English Language Course Curriculum Based on Tyler’s Model from the Students’ Perspective at Birjand University of Medical Sciences - Yahya Mohammadi; Nargess Hekmati; Hossein Navidinia (مجله دانشگاه علوم پزشکی بیرجند, 2018)
Background and Aim: Although evaluation has been considered as an inseparable part of education, evaluating higher education curriculum in most of the university programs has not been adequately investigated. The purpose of the present study is to investigate the quality of general English language course curriculum and English language learning based on Tyler’s Model from the students’ perspective at Birjand University of Medical Sciences. Materials and Methods: This study was descriptive – analytic. The participants were students having General English course at Birjand University 180 students were randomly selected based of Medical Sciences. A total of on Krejcie and Morgan table. Data collection was done through a researcher-made questionnaire including 28 items. The validity of the questionnaire was confirmed by experts in medical and English language education and the reliability was estimated as 82% based on Cronbach's alpha. Data were analyzed in SPSS software using descriptive (frequency and percentage) and inferential statistics (one sample T-test). Results: The results indicated that the experimental mean score was higher than the theoretical one, and there was a significant difference (p < 0.05) between the two means in three aspects of ‘content’, ‘teaching methods’, and ‘evaluation’ in general English course. Also, the experimental mean in the aspect of ‘course goals’ was less than the theoretical mean and there was a significant difference between them (p > 0.05). Conclusion: Based on the results of this study, the goals of general English language course should be reevaluated so it can satisfy the students’ needs.